Choosing Wisely: Adherence by Physicians to Recommended Use of Spirometry in the Diagnosis and Management of Adult Asthma - Sokol, Kristin C.; Sharma, Gulshan; Lin, Yu-Li; Goldblum, Randall M. (The American journal of medicine, 2015)
The National Asthma Education and Prevention Program (NAEPP) and the American Thoracic Society provide guidelines stating that physicians should use spirometry in the diagnosis and management of asthma. The aim of this study was to evaluate the trends, over a 10-year period, in the utilization of spirometry in patients newly diagnosed with asthma. We hypothesized that spirometry use would increase in physicians who care for asthma patients, especially since 2007, when the revised NAEPP guidelines were published. This retrospective cohort analysis of spirometry use in subjects newly diagnosed with asthma used a privately insured adult population for the years 2002-2011. Our primary outcome of interest was spirometry performed within a year (± 365 days) of the initial date of asthma diagnosis. We also examined the type of asthma medications prescribed. In all, 134,208 patients were found to have a diagnosis of asthma. Only 47.6% had spirometry performed within 1 year of diagnosis. Younger patients, males, and those residing in the Northeast were more likely to receive spirometry. Spirometry use began to decline in 2007. Patients cared for by specialists were more likely to receive spirometry than those cared for by primary care physicians; 80.1% vs 23.3%, respectively. Lastly, even without spirometry, a significant portion of patients (78.3%) was prescribed asthma drugs. Our study suggests that spirometry is underutilized in newly diagnosed asthma patients. Moreover, the use of controller medications in those diagnosed with asthma without spirometry remains high.